Macroeconomic Adjustments Under the Pitfalls of Quantitative Easing in the EU: Balancing Economic Growth and Inflation Across Monetary Regimes - Stojkov, Stefan; Beker Pucar, Emilija; Sekulić, Aleksandar (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Institutional governance, along with economic development, plays a pivotal role in ensuring the effective transmission of quantitative easing (QE). This research aims to evaluate the efficiency of QE in stimulating gross domestic product (GDP) while simultaneously considering the impact on prices in the EU from a trade-off perspective over the 2014Q1-2023Q1 time horizon. The research is based on macro-panel data differentiating EU countries from the angle of monetary autonomy: EZ members (Austria, Belgium, France, Germany, Netherlands, Italy, and Spain) and emerging monetary autonomous EU economies (Czech, Hungary, Poland, and Romania). Empirical findings are based on the framework of non-stationary, heterogeneous, dynamic panels using a Pooled Mean Group (PMG) estimator to test whether QE’s impact on GDP is strong enough to elevate prices. Our findings suggest that monetary convergence guaranteed EZ members stable economic conditions through adjustment and discipline. In contrast, the monetary flexibility of autonomous countries resulted in higher prices which subsequently hindered economic growth.